Significant association between rare IPO11‐HTR1A variants and attention deficit hyperactivity disorder in Caucasians. Issue 7 (16th June 2015) - Zuo, Lingjun; Saba, Laura; Lin, Xiandong; Tan, Yunlong; Wang, Kesheng; Krystal, John H.; Tabakoff, Boris; Luo, Xingguang
Abstract : We comprehensively examined the rare variants in the IPO11‐HTR1A region to explore their roles in neuropsychiatric disorders. Five hundred seventy‐three to 1, 181 rare SNPs in subjects of European descent and 1, 234–2, 529 SNPs in subjects of African descent (0 < minor allele frequency (MAF) < 0.05) were analyzed in a total of 49, 268 subjects in 21 independent cohorts with 11 different neuropsychiatric disorders. Associations between rare variant constellations and diseases and associations between individual rare variants and diseases were tested. RNA expression changes of this region were also explored. We identified a rare variant constellation across the entire IPO11‐HTR1A region that was associated with attention deficit hyperactivity disorder (ADHD) in Caucasians (T5: P = 7.9 × 10 −31 ; Fp: P = 1.3 × 10 −32 ), but not with any other disorder examined; association signals mainly came from IPO11 (T5: P = 3.6 × 10 −10 ; Fp: P = 3.2 × 10 −10 ) and the intergenic region between IPO11 and HTR1A (T5: P = 4.1 × 10 −30 ; Fp: P = 5.4 × 10 −32 ). One association between ADHD and an intergenic rare variant, i.e., rs10042956, exhibited region‐ and cohort‐wide significance ( P = 5.2 × 10 −6 ) and survived correction for false discovery rate (q = 0.006). Cis ‐eQTL analysis showed that, 29 among the 41 SNPs within or around IPO11 had replicable significant regulatory effects on IPO11 exon expression (1.5 × 10 −17 ≤ P < 0.002) in human brain or peripheral blood mononuclear cell tissues. We concluded that IPO11‐HTR1A was a significant risk gene region for ADHD in Caucasians. © 2015 Wiley Periodicals, Inc.